Experimental elevation of wildlife testosterone using silastic tube implants. (October 2016) - Koresh, Efrat; Matas, Devorah; Koren, Lee
Abstract: Testosterone (T) is a key androgen that mediates vertebrate molecular, cellular, and behavioral processes. Its manipulation is therefore of interest to a vast number of researchers studying animal behavior and reproduction, among others. Here, the usage of silastic implants across wildlife species is reviewed, and a method to manipulate rock hyrax ( Procavia capensis ) testosterone levels using silastic implants is presented. Using a series of in-vitro and in-vivo experiments, the secretion patterns of silastic tubes and silastic glue were tested and were surprisingly found to be similar. In addition, we studied endogenous T levels in wild-captured rock hyraxes ( Procavia capensis ), and using T implants succeeded in elevating T to the maximal physiological concentrations recorded during the mating period. The number of implants that were inserted was the only predictor of T levels, and seven 20 mm implants were found to be the optimal dose. Implants induced sexual behaviors in the non-reproductive period. The duration of time that the implants were in the hyrax was the only significant factor that influenced the amount of T left over in the implant once it was removed. All together we affirm that T implants may offer a versatile tool for wildlife behavioral research by elevating T levels in the non-breeding period to maximal breeding levels. Graphical abstract: Testosterone levels for hyrax with seven implants achieved the maximal breeding level at the non-breeding season. For the hyrax picture all rights reserved to Massada Ltd. Highlights: We review the usage of testosterone manipulation via silastic implants in wildlife. In-vitro, testosterone is secreted from silastic implants covered with silastic glue. We used silastic implants to elevate testosterone in rock hyrax. Seven 20 mm implants elevated testosterone to maximal physiological concentrations. Testosterone implants may offer a versatile tool for wildlife behavioral research.